The dynamics of the alternatively spliced NOL7 gene products and role in nucleolar architecture - Kinor, Noa (Landes Bioscience, 2011)
Three alternatively spliced forms of the human NOL7 gene coding for relatively small proteins were identified. The two shorter forms were generated by intron retention events, and each isoform was differently localized within the cell. The NOL7-SP1 long form (29 kD) localized to the nucleolus, SP2 was nucleoplasmic, while SP3 was distributed throughout the whole cell. NOL7-SP1 was confined to the nucleolar granular component, and during cell division disassociated from the nucleolus. Knockdown of NOL7-SP1 levels abrogated nucleolar architecture, in particular the internal regions, and reduced cell proliferation. Analysis of the nucleolar dynamics of the SP1 protein during interphase showed nucleolar high binding affinity. Dissection of protein domains showed that nucleolar targeting was mediated by a unique C-terminal nucleolar localization sequence (NoLS). However, this sequence was not sufficient for conferring high binding affinity, which required additional regions of the protein. Our analysis shows that NOL7 is important for maintaining internal nucleolar structure and cell growth rates, and that while specific protein localization can be obtained by specific short localization motifs, nucleolar residency through binding must be mediated by a synergistic combination of protein modules.